Novel Frameshift Autosomal Recessive Loss-of-Function Mutation inSMARCD2Encoding a Chromatin Remodeling Factor Mediates Granulopoiesis - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (SPRINGER/PLENUM PUBLISHERS, 2021)
Purpose Recently, a new form of congenital neutropenia that is caused by germline biallelic loss-of-function mutations in theSMARCD2gene was described in four patients. Given the rarity of the condition, the clinical spectrum of the disease has remained elusive. We here report a new patient with a novel frameshift mutation and compare our patient with the previously reportedSMARCD2-mutant patients, aiming to provide a more comprehensive understanding of the natural course of the disease. Methods Clinical and laboratory findings of all reported patients were reviewed. Next-generation sequencing was performed to identify the causative genetic defect. Data on the hematopoietic stem cell transplantation including stem cell sources, conditioning regimen, engraftment, graft-versus-host disease, and infections were also collected. Results An 11-year-old female patient had a variety of infections including sepsis, deep tissue abscesses, otitis, pneumonia, gingivitis, and diarrhea since infancy. A novel homozygous mutation inSMARCD2(c.93delG, p.Ala32Argfs*80) was detected. Bone marrow examination showed hypocellularity and decreased neutrophils with diminished granules and myeloid dysplasia, but no blast excess as in previously reported patients. The neutropenia was non-responsive even to higher doses of granulocyte colony-stimulating factor (G-CSF); therefore, the patient was transplanted at 10 years of age from a HLA-A allele-mismatched unrelated donor using a reduced toxicity conditioning regimen and recovered successfully. Compared with the previous four cases, our patient showed longer survival before transplantation without blastic transformation. Conclusion Distinctive myeloid features and long-term follow-up including therapy options are presented for the newly described case of SMARCD2 deficiency. This disorder is apparent at infancy and requires early transplantation due to the unrelenting disease course despite conventional therapy.
Keywords: SMARCD2; SWI; SNF complex; CEBPE; neutropenia; specific granule deficiency; hematopoietic stem cell transplantation; CONGENITAL NEUTROPENIA; GRANULE DEFICIENCY; PATIENT